Mechanical Strength and Microstructure of Soft Soil Stabilized with Cement, Lime, and Metakaolin-Based Geopolymer Stabilizers - Tadesse Abebe Wassie; Gökhan Demir (Advances in Civil Engineering)
Soft soils require particular consideration when designing civil engineering structures due to their high compressibility, low shear strength, and permeability. Using chemical additives and geopolymers to stabilize soft soils is a practical approach to improve their engineering properties. The objective of the study was to explore the use of conventional stabilizers alongside metakaolin-based geopolymers. This study also aimed to investigate the compaction characteristics, mechanical strength, shear behavior, and microstructure of stabilized soft soil. The compaction test was carried out using various amounts of cement (6%, 8%, and 10%) and metakaolin (3%, 5%, and 7%) based on the dry weight of the soil. Cement, lime, and geopolymer were added to the soft soil at 15% of the dry weight of the soil for triaxial shear tests. The compaction test results indicated that the stabilized soil exhibited the highest maximum dry density at 8% cement content. Adding metakaolin (MK) to the cement-modified soil decreased the maximum dry density, smoothed the compaction curve, and increased the optimum moisture content. The unconfined compressive strength (UCS) test revealed that cement-stabilized soil had the highest yield stress, while adding MK to the cement-modified soil reduced the yield stress after 7 days of curing. Compared to untreated soft soil, there was a significant increase in shear strength parameters for cement-, metakaolin-, and lime-stabilized soil. This study demonstrates that adding chemical additives and geopolymers can improve the soft soil’s compaction characteristics, mechanical strength, and shear strength parameters.